A Review on Various Techniques for Boron Recovery: Focusing on Efficiency, Sustainability, Scalability, and Cost-Effectiveness - Memon, Muhammad Faseeh; Memon, Zubair Ahmed; Ahmed, Omar Shabbir (Journal of Ecohumanism, 2024)
Boron is a critical element extensively used across various industries—such as glass manufacturing, ceramics, agriculture, detergents, nuclear energy, and aerospace—due to its unique chemical and physical properties. However, its widespread industrial use has raised significant environmental concerns, particularly its accumulation in aquatic systems, posing risks to biodiversity, plant life, and human health. This review examines the impacts of boron pollution on aquatic organisms, plants, and humans, highlighting the necessity for effective recovery strategies. We provide a comprehensive analysis of boron recovery techniques—such as reverse osmosis, electrodialysis, nanofiltration, adsorption, membrane distillation, and leaching—focusing on their efficiency, sustainability, scalability, and cost-effectiveness. The evaluation compares each method’s operational parameters, environmental impact, and economic feasibility. While methods like reverse osmosis and electrodialysis offer high removal efficiencies, they are often limited by operational costs and environmental drawbacks. Alternative methods like adsorption and nanofiltration present more sustainable and cost-effective options but may require optimization for large-scale applications. This review underscores the need for advanced, economically viable, and sustainable boron recovery technologies to mitigate environmental risks and comply with regulatory standards.